Association between GSTM1 and GSTT1 polymorphisms and susceptibility to methamphetamine dependence - Khalighinasab, Mohammad Rashid (Mol Biol Res Commun, 2015)
Glutathione S-transferases (GSTs; EC: 2.5.1.18) are ubiquitous multifunctional enzymes, which play a key role in cellular detoxification. Functional genetic polymorphisms in genes encoding GSTM1 (a member of GST class mu; OMIM: 138350), and GSTT1 (a member of GST class theta; OMIM: 600436) have been well defined. The functional null alleles of GSTM1 and GSTT1 represent deletions of GSTM1 and GSTT1 genes, respectively. The aim of the present study is to investigate the association between GSTM1 and GSTT1 polymorphisms and methamphetamine dependence. The present population-based case-control study was performed in Shiraz (southern Iran). In total, 52 methamphetamine dependence (11 females, 41 males) and 635 healthy controls (110 females, 525 males) were included in this study. The genotypes of GSTM1 and GSTT1 polymorphisms were determined by PCR. Neither GSTM1 (OR=0.92, 95% CI: 0.52-1.61, P=0.771) nor GSTT1 (OR=0.71, 95% CI: 0.33-1.54, P=0.381) null genotypes were significantly associated with risk of methamphetamine dependence. It should be noted that although there was no association between the GSTM1 null genotype and risk of methamphetamine dependence, in both genders, there was significant interaction between gender and GSTM1 polymorphism (P=0.029). The combination genotypes of the GSTM1 and GSTT1 polymorphisms revealed that the genotypes of these two polymorphisms had no additive effect in relation to the susceptibility to methamphetamine dependence. The present study revealed that genetic polymorphisms of GSTT1 and GSTM1 are not risk factors for methamphetamine dependence.